Collaboration of Architects in Providing Social Facilities After The 2018-2019 Earthquake Disaster in Lombok Case Study : Community Learning Centre, Rembitan – Central Lombok, NTB (2019) - Teddy Aria Permana Noerkamiden; R.A. Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
After the 2018 earthquake disaster in Central Lombok Regency, West Nusa Tenggara, various recovery efforts have been carried out involving support from local, national, and international levels in the 2018-2019 period. The impact of losses, both in the form of materials and casualties, is enormous, with total infrastructure damage estimated at Rp 9.1 billion1. In the context of accelerating rehabilitation and reconstruction, architects play a role as key agents who act as balancers, catalysts, and harmonisers in the process of rebuilding affected communities. This research is based on the activities of the Indonesian Institute of Architects (IAI) East Java Province 2 and Titian Foundation 3, focusing on providing assistance to affected communities in Rembitan Village, Pujut Sub-district, Central Lombok, through the planning and construction of a Community Learning Centre (CLC) 4 in the 2019-2020 period. This assistance includes professional assistance to ensure the building is built in accordance with its recovery objectives. Using contextual-based qualitative research methods and comparative analysis, this study aims to re-evaluate the process of community recovery through physical infrastructure development. In particular, a new built environment that is based on the daily activities of the local community is expected to provide significant changes in rehabilitation and reconstruction efforts. By integrating all of the above elements, the CLC can become a place that encourages the creation of a resilient community. The CLC not only functions as a place of learning, but also as a centre for community coordination and support in dealing with disasters. Through adaptive design, good collaboration, and the utilisation of local resources, CLCs can help communities to be better prepared for unexpected challenges, reduce vulnerability, and increase resilience and adaptability. With resilient CLCs in place, communities can learn to not only survive, but also thrive in the face of upcoming changes and challenges.